2007
DOI: 10.1002/prot.21555
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of helix packing in transmembrane dimer of the cell death factor BNIP3: A molecular modeling study

Abstract: BNIP3 is a mitochondrial 19-kDa proapoptotic protein, a member of the Bcl-2 family. It has a single COOH-terminal transmembrane (TM) alpha-helical domain, which is required for membrane targeting, proapoptotic activity, hetero- and homo-dimerization in membrane. The role and the molecular details of association of TM helices of BNIP3 are yet to be established. Here, we present a molecular modeling study of helix interactions in its membrane domain. The approach combines Monte Carlo conformational search in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…This result is not surprising since spontaneous helix-helix aggregations were already observed in nanosecond time simulations, providing that the starting configurations are not too far away [13,14]. On the other hand, 4 out of 10 simulations performed in water, for a total of about 120 ns, did not produce a parallel pairing of the two helices.…”
Section: Igtm Helix-helix Association Structure and Stabilitysupporting
confidence: 40%
See 1 more Smart Citation
“…This result is not surprising since spontaneous helix-helix aggregations were already observed in nanosecond time simulations, providing that the starting configurations are not too far away [13,14]. On the other hand, 4 out of 10 simulations performed in water, for a total of about 120 ns, did not produce a parallel pairing of the two helices.…”
Section: Igtm Helix-helix Association Structure and Stabilitysupporting
confidence: 40%
“…In particular, MD simulations can provide useful insights into the factors governing helix-helix association in lipid bilayers. Although incomplete sampling, inaccurate force fields, and approximate treatment of long-range interactions intrinsically limit these studies, intriguing results on the mechanisms of TM helix recognition have been recently reported [13,14,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that the NH 2 and COOH termini of Bnip3 cooperate in the homodimerization and activation of Bnip3. Interestingly, based on structural analysis of the transmembrane domain using NMR and computational modeling, it has been proposed that the Bnip3 homodimer may be able to form a channel that is permeable to water (4,33). However, it still remains to be determined whether the activated homodimer forms a channel in the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the transmembrane domain completely abrogates homodimerization and cell death (7), although this might be due to the fact that the transmembrane domain is also important for targeting Bnip3 to the mitochondria. Computational modeling and mutagenesis studies (4,29,33) have identified the histidine at residue 173 to be essential for homodimerization of Bnip3. Our study confirms the importance of the histidine at residue 173 in homodimerization and also demonstrates that this residue is essential for the cell death activity of Bnip3.…”
Section: Discussionmentioning
confidence: 99%
“…Correctness of the resulting 'consensus' structures was assessed based on the information about orientation of the CO groups determined by site-specific infrared dichroism. Vereshaga et al, 2007, calculated the spatial structure of TM segment dimer of human proapoptotic protein Bnip3. In this case, Monte Carlo conformational search in an implicit membrane with subsequent MD relaxation of the best models in the full-atom DMPC bilayer was used for identification of the potential structures.…”
mentioning
confidence: 99%